Integration of substrate- and flow-derived stresses in endothelial cell mechanobiology - Claire A. Dessalles (Nature Portfolio, 2021)
Dessalles et al review the responses of vascular endothelial cells to mechanical forces exerted by both blood flow and physical contact with the basement membrane. Special attention is paid to how endothelial cells respond to multiple mechanical cues that are exerted simultaneously.